2014
DOI: 10.1177/1403494814561817
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in co-occurrence of depressive and anger symptoms among adolescents in five Nordic countries

Abstract: The findings underline the need for attending to both depressive and anger symptoms among adolescents when designing mental health interventions and treatments as co-occurrence of both types of symptoms is common, particularly among females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
10
1
3
Order By: Relevance
“…Among adolescents, continuous analgesic use for reducing pain in association with depressive symptoms could prevent them from learning healthier strategies for coping with stress and depressive symptoms while progressing into and through adulthood (Holmström et al, 2014;Skarstein, Lagerløv, Kvarme, & Helseth, 2018). Moreover, the data present similar results in which female students expressed more depressive symptoms than male students (Asgeirsdottir & Sigfusdottir, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…Among adolescents, continuous analgesic use for reducing pain in association with depressive symptoms could prevent them from learning healthier strategies for coping with stress and depressive symptoms while progressing into and through adulthood (Holmström et al, 2014;Skarstein, Lagerløv, Kvarme, & Helseth, 2018). Moreover, the data present similar results in which female students expressed more depressive symptoms than male students (Asgeirsdottir & Sigfusdottir, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…This finding is not, however, a new one; the tendency has been reported repeatedly in Finnish community studies [52,53]. Moreover, in a recent cross-national study of more than 8000 adolescents from different Nordic countries, girls reported significantly more anger symptoms than boys did [54]. According to some researchers, this phenomenon may reflect the social, educational and economic gender equality characteristics of Nordic countries [53].…”
Section: Gender Differences In Descriptive Statisticsmentioning
confidence: 79%
“…Respecto a las mujeres, una vez parcializado el efecto de la depresión, los tres factores de la alexitimia contribuyen a la relación con la violencia; y la relación de la alexitimia se da con la violencia sufrida, pero no con la violencia ejercida. Para que la relación entre alexitimia y violencia ejercida sea significativa en mujeres, debe estar presente la depresión, lo que probablemente esté motivado por un humor irritable e incluso por una baja autoestima, que permite reconocer un rasgo socialmente no deseable en la mujer, como el ser violenta e irascible (Asgeirsdottir & Sigfusdottir, 2014). Las asociaciones de la alexitimia con la frecuencia y el daño sufridos fueron muy semejantes una vez parcializada la depresión; cuando, sin tal parcialización, las correlaciones con daño eran mayores, lo que refleja el efecto sensibilizador de la depresión en el reporte del daño.…”
Section: Discussionunclassified
“…Así, la depresión parece desinhibir la conducta violenta, sobre todo en mujeres, probablemente desde el humor irritable asociado a la de-presión. Asimismo, la baja autoestima asociada a la depresión podría facilitar el reconocer un rasgo socialmente no deseable en la mujer como el ser violenta e irascible (Asgeirsdottir & Sigfusdottir, 2014). Aunque el modelo estructural muestra variación entre los sexos, los modelos por sexo coinciden en mostrar el efecto directo de que la alexitimia sobre la violencia ejercida es espurio y está totalmente mediado por la depresión en mujeres y por la violencia recibida en hombres.…”
Section: Discussionunclassified
See 1 more Smart Citation